Topdressing Sand Color, Cultivation Timing, and Cultivation Method Effects on Disruption of a Creeping Bentgrass Golf Green in the Intermountain Pacific Northwest. Issue 1 (12th January 2013) - Proctor, Christopher A.; Johnston, William J.; Golob, Charles T.; Stahnke, Gwen K.; Williams, Matthew W.
Abstract : Cultivation and topdressing are commonly used methods to manage thatch/mat on creeping bentgrass ( Agrostis stolonifera L.) golf greens. However, disruption caused by cultivation practices may adversely impact the playability of golf green surfaces. Thus, we undertook two studies to determine if sand topdressing color affects recovery from cultivation disruption of creeping bentgrass golf greens. Topdressing sand color treatments were black sand (BS) or tan sand (TS). Study 1 evaluated six cultivation methods and topdressing with TS or BS in 2008, 2009, and 2010. Plots were evaluated for total days disrupted (TDD) and mean days disrupted following cultivation (MDD). Topdressing with BS never resulted in more TDD than TS and decreased TDD for some cultivation treatments. Study 2 evaluated days to recover (DTR) following cultivation and topdressing with TS or BS at twelve aeration dates in 2008 and 2009. Black sand never resulted in more DTR than TS during any year and produced fewer DTR at one aeration date in 2008 and two aeration dates in 2009. We found that BS has potential to decrease recovery time following cultivation, but depends on cultivation timing and method. Optimizing cultivation timing, cultivation method, and topdressing sand, disruption time following cultivation can be reduced for creeping bentgrass putting greens in the Intermountain Pacific Northwest.